2000
DOI: 10.1097/00004424-200010000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral Bone and Cartilage Disease

Abstract: The role of subchondral bone in the pathogenesis of cartilage damage has likely been underestimated. Subchondral bone is not only an important shock absorber, but it may also be important for cartilage metabolism. Contrary to many drawings and published reports, the subchondral region is highly vascularized and vulnerable. Its terminal vessels have, in part, direct contact with the deepest hyaline cartilage layer. The perfusion of these vessels accounts for more than 50% of the glucose, oxygen, and water requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(193 citation statements)
references
References 21 publications
2
176
0
9
Order By: Relevance
“…It has been suggested that they may represent different consecutive phases of the degenerative process in the subchondral marrow [3,17]. The importance of the endplate [21,22] and subchondral bone [8] for the integrity of the intervertebral disc has been pointed out. An injury to the vertebral body endplate has been found to provide a potent mechanical stimulus for disc degeneration [20] and tissue trauma following fracture has been suggested to cause accelerated intervertebral disc degeneration [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that they may represent different consecutive phases of the degenerative process in the subchondral marrow [3,17]. The importance of the endplate [21,22] and subchondral bone [8] for the integrity of the intervertebral disc has been pointed out. An injury to the vertebral body endplate has been found to provide a potent mechanical stimulus for disc degeneration [20] and tissue trauma following fracture has been suggested to cause accelerated intervertebral disc degeneration [10].…”
Section: Discussionmentioning
confidence: 99%
“…A microtrauma to the endplate has been suggested to be the initiating event for a progressive deteriorating process with inflammatory or autoimmune effects, by allowing a contact between the noxious substances in the degenerative disc and cells in the bone matrix via the injured endplate [1,20]. An endplate defect may also develop as a non-specific reaction to an insufficient healing process, beginning with bone marrow edema and necrosis [8]. An inflammatory process in endplates with M1 subchondral signal changes has been suggested to be induced by tumor necrosis factor (TNF) [18].…”
Section: Discussionmentioning
confidence: 99%
“…But, is this so? The work of Imhof and others has shown our classical teaching of the impermeable osteochondral junction is not correct [26]. By revisiting the histology of this region, the conclusion is drawn that the terminal vessels in the richly supplied subchondral zone of normal mature bone directly contact the deepest hyaline cartilage layer.…”
Section: So Where Does the Problem Lie?mentioning
confidence: 96%
“…Only 1-3% of load forces are attenuated by cartilage while the normal subchondral bone is able to attenuate about 30% of the load through the joints. (Imhof, Sulzbacher et al, 2000) The subchondral bone protects the articlar cartilage from damage caused by excessive loading. The condylar ear and the articular fossa receive their blood supply from arteries supplying the underlying bone.…”
Section: Composition Of the Synovial Fluidmentioning
confidence: 99%